Immune modulation: the key to combat SARS-CoV-2 induced myocardial injury - Zhaoqing Li; Luning Qin; Xiaojian Xu; Ruolan Chen; Guoliang Zhang; Banghui Wang; Bing Li; Xian-Ming Chu; Xian-Ming Chu (Frontiers in Immunology)
The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which caused the Coronavirus disease 2019 (COVID-19) pandemic, has posed significant healthcare challenges. In addition to respiratory complications, it has led to severe damage in other organs, particularly the cardiovascular system. Of which, myocardial injury is increasingly recognized as a most significant complication, contributing to the high mortality. Recent research indicates the pivotal role of immune dysregulation in mediating myocardial injury in patients infected with SARS-CoV-2. In this review, we provide a comprehensive analysis of the immune mechanisms involved in SARS-CoV-2-induced myocardial damage, focusing on the roles of key immune cells and molecules that contribute to this pathological process. Aiming at mitigating the myocardial injury of COVID-19, we review immune-based treatments under evaluation in preclinical and clinical trials. Along with talking about the similarities and differences in myocardial injury resulting from SARS-CoV-2, the Middle East respiratory syndrome coronavirus (MERS-CoV) and the severe acute respiratory syndrome coronavirus (SARS-CoV). This article provides a unique perspective on using past experiences to prevent myocardial injury in the face of ongoing virus mutations.